1996
DOI: 10.1002/bjs.1800831229
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A and multiple fibroadenomas of the breast

Abstract: Multiple bilateral fibroadenomas are uncommon. This finding in four women who had received renal transplants prompted further inquiry. A prospective study was performed on 39 women under the age of 55 years who had received a renal transplant at least 1 year earlier. Clinical examination and breast ultrasonography were performed. Factors considered included immunosuppressive therapy, concurrent medication and renal function. Blood was taken for estimation of oestradiol, prolactin, follicle-stimulating hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…The presence of a mouse mammary tumor virus in rodents and published reports of HIV-positive rapidly growing breast cancers suggest a possible viral etiology for some breast cancers (10,16). One study reported multiple and bilateral fibroadenomas in immunosuppressed patients receiving cyclosporin A (17). Isolated studies have investigated the EBV/breast cancer association with contradictory results (2,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a mouse mammary tumor virus in rodents and published reports of HIV-positive rapidly growing breast cancers suggest a possible viral etiology for some breast cancers (10,16). One study reported multiple and bilateral fibroadenomas in immunosuppressed patients receiving cyclosporin A (17). Isolated studies have investigated the EBV/breast cancer association with contradictory results (2,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…For example, gingival hypertrophy occurs commonly, and patients frequently require oral surgery to correct it; cyclosporin A is thought to affect the gingival fibroblasts directly to promote both proliferation and collagen production. 12 A positive relationship has been reported between the use of cyclosporin A and the prevalence of multiple giant fibroadenomas of the breast, 8,9 but to our knowledge, no association between the presence of gingival hypertrophy and the presence of fibroadenomas has been reported. This implies that the mechanism of action of cyclosporin A in promoting the development of breast fibroadenomas differs from its action on the gingiva.…”
Section: Discussionmentioning
confidence: 81%
“…Unlike the cases in our study, none of those 12 cases involved giant fibroadenomas. In the study by Baildam et al, 8 fibroadenomas were seen in 13 of 29 women with kidney transplants who had undergone cyclosporin A therapy; 10 of those 13 cases involved multiple lesions and, in 5, the lesions were bilateral. No breast abnormalities were recorded in the 10 women treated with steroids and azathioprine alone.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations